PENGARUH FASILITAS PERPUSTAKAAN TERHADAP KEPUASAN PEMUSTAKA DI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SULAWESI SELATAN - Anugrah Wardani, Anggi; Ohan, Faridah; Hastuti, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effect of library facilities on user satisfaction at the South Sulawesi Provincial Library and Archives Service. The problem underlying this research is the importance of adequate library facilities in supporting users’ comfort, ease of access to information, and overall satisfaction, particularly amid the development of technology and the increasing need for quality library services. This study aims to describe the condition of library facilities, describe user satisfaction, and analyze the effect of library facilities on user satisfaction at the South Sulawesi Provincial Library and Archives Service. This research employed a quantitative approach with a causal associative research design. The population consisted of library users who utilized the facilities at the South Sulawesi Provincial Library and Archives Service. The sample was selected using accidental sampling, involving 135 respondents. Data were collected through questionnaires and analyzed using descriptive statistical analysis and inferential statistical analysis with simple linear regression. The results showed that library facilities were categorized as very good, and user satisfaction was also categorized as very good. Furthermore, the results indicated that library facilities had a positive and significant effect on user satisfaction. These findings indicate that the better the library facilities provided, the higher the level of satisfaction experienced by library users. Therefore, improving and maintaining the quality of library facilities is important to support the effectiveness of library services and meet users’ needs and expectations.